Analisis Kesiapan Kurikulum Indonesia Dalam Menghadapi Persaingan Global - Musanadah, Siti; Dwiyanti, Fadia Risqi; Manihtada, Ihda; Zulfahmi, Muhammad Nofan (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Abstract_______________________________________________________________This study analyzes the readiness of the education curriculum in Indonesia in facing increasingly complex global competition. The curriculum has a strategic role in increasing the nation's competitiveness, especially with the demands of 21st-century skills such as critical thinking, collaboration, creativity, and mastery of technology. With a literature study approach, this study evaluates the strengths and weaknesses of the Indonesian curriculum, including the implementation of the Merdeka Curriculum which aims to increase learning flexibility. Despite progressive steps, challenges such as infrastructure gaps, minimal teacher training, and low mastery of technology and foreign languages are still major obstacles. The results of the analysis show the importance of integrating global values such as sustainability, inclusiveness, and interdisciplinary competence in the curriculum. In addition, collaboration between the world of education and industry is needed to ensure the relevance of the curriculum to the needs of the job market.